2008
DOI: 10.1111/j.1526-4637.2007.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

What Percentage of Chronic Nonmalignant Pain Patients Exposed to Chronic Opioid Analgesic Therapy Develop Abuse/Addiction and/or Aberrant Drug-Related Behaviors? A Structured Evidence-Based Review

Abstract: The results of this evidence-based structured review indicate that COAT exposure will lead to abuse/addiction in a small percentage of CPPs, but a larger percentage will demonstrate ADRBs and illicit drug use. These percentages appear to be much less if CPPs are preselected for the absence of a current or past history of alcohol/illicit drug use or abuse/addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
352
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(366 citation statements)
references
References 90 publications
6
352
0
8
Order By: Relevance
“…Another meta-analysis conducted to determine the percentage of CNCP patients exposed to COT develop addiction and/ or aberrant drug-related behaviors concluded that Bthe results of this evidence-based structured review indicate that COT exposure will lead to abuse/addiction in a very small percentage of patients. This percentage can be dramatically decreased by preselecting CNCP patients, who have no previous/current history of drug/alcohol abuse/addiction^ [8]. Aberrant drug-related behavior (ADRB) rates in the range of 15 % seem more realistic than addiction rates.…”
Section: Chronic Pain and Opioid Therapymentioning
confidence: 99%
“…Another meta-analysis conducted to determine the percentage of CNCP patients exposed to COT develop addiction and/ or aberrant drug-related behaviors concluded that Bthe results of this evidence-based structured review indicate that COT exposure will lead to abuse/addiction in a very small percentage of patients. This percentage can be dramatically decreased by preselecting CNCP patients, who have no previous/current history of drug/alcohol abuse/addiction^ [8]. Aberrant drug-related behavior (ADRB) rates in the range of 15 % seem more realistic than addiction rates.…”
Section: Chronic Pain and Opioid Therapymentioning
confidence: 99%
“…A case in point is provided by Richard Feynman, a Nobel laureate in physics, who stopped drinking alcohol upon noticing that it was becoming involuntary--because he felt that it would be threatening the pleasure he derived from his thinking [51]. Tellingly, among individuals exposed to chronic opioid analgesic therapy (COAT), less than 0.1 % becomes addicted de novo, while overall illicit drug use among COAT patients does not exceed its prevalence in the general population [52].…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…[3] Results of a structured evidence-based review suggest that abuse develops in <5% of chronic pain patients treated with prescription opioid analgesics, although rates of abuse varied considerably across individual studies. [4] Nevertheless, it is estimated that approximately 33 million people -or 0.7% of the world's adult population -currently abuse prescription or nonprescription opioids. [2] In 2014, approximately 4.3 million individuals aged 12 years or older (1.6% of the population aged 12 or older) reported non-medical use of prescription opioid analgesics in the USA, making prescription opioid analgesics the second most commonly abused drug class after marijuana.…”
Section: Introductionmentioning
confidence: 99%